Dear Every one,
I need some help converting rectanglur implicit equation to polar equation:
9*(x^2+y^2)=(x^2+y^2-2y)^2. and I know the fact of r=\sqrt(x^2+y^2) and tan \theta=y/x, where x is not equal to 0.
Thank you for your help,
Dear Every one,
I need some help converting rectanglur implicit equation to polar equation:
9*(x^2+y^2)=(x^2+y^2-2y)^2. and I know the fact of r=\sqrt(x^2+y^2) and tan \theta=y/x, where x is not equal to 0.
Thank you for your help,
Hello, Cbarker1!
So you know that: .$\displaystyle x^2 + y^2 \:=\:r^2$
Do you also know this? . $\displaystyle \begin{Bmatrix}x &=& r\cos\theta \\ y &=& r\sin\theta\end{Bmatrix}$
What's stopping you?$\displaystyle \text{Convert to polar form: }\: 9(x^2+y^2)\:=\:(x^2+y^2-2y)^2$
$\displaystyle 9\underbrace{(x^2+y^2)}_{r^2} \;=\;(\underbrace{x^2+y^2}_{r^2} - 2\underbrace{y}_{r\sin\theta})^2$
. . . . . $\displaystyle 9r^2 \;=\;(r^2 - 2r\sin\theta)^2$